Electrocatalysis of oxygen reduction reaction on gold nanoparticles modified titanium dioxide films with different morphology - Maltanava, Hanna M.; Brezhneva, Nadzeya Yu.; Mazanik, Alexander V.; Mazheika, Semyon O.; Gaevskaya, Tatiana V.; Skorb, Ekaterina V.; Poznyak, Sergey K. (Journal of the Belarusian State University. Chemistry, 2020)
Dense and mesoporous titanium dioxide films have been obtained on titanium substrate by means of thermal oxidation, hydrolysis of polybutyltitanate, deposition of titanium dioxide sol, ultrasonic treatment and anodic oxidation and characterized by scanning electron microscopy, transmission electron microscopy and Raman spectroscopy. Electrochemical activity of titanium dioxide films, initial and modified by gold nanoparticles, in oxygen reduction reaction (ORR) in alkaline medium has been studied by cyclic voltammetry. It has been demonstrated that the efficiency of the dense and mesoporous titanium dioxide films in ORR is determined by their morphology, structure and pore ordering degree. Modification of titanium dioxide films by gold nanoparticles results in the decrease in overpotential of the ORR. It has been found that the electrodes consisted of highly ordered layers of titania nanotubes with deposited gold nanoparticles demonstrate sufficiently higher electrocatalytic activity toward the oxygen electroreduction in comparison with TiO2/Au systems based on dense films and mesoporous films with disordered pore structure. Features of electrochemical behavior of TiO2/Au (nanotubes/nanoparticles) system are explained by the peculiarities of electron transport to the electrode surface and structure of space charge layer in the mesoporous oxide film.